- 3


G (7. 4)-

 

1

0

0

0

1

1

0

 

G(7,4) =

0

1

0

0

0

1

1

.

0

0

1

0

1

1

1

(1.14)

 

0

0

0

1

1

0

1

 

:

 

 

1

0

0

0

1

1

0

 

U

= m× G = ( m0 m1 m2 m3 )

0

1

0

0

0

1

1

=

 

0

0

1

0

1

1

1

 

 

0

0

0

1

1

0

1

 

 

= (m0 , m1 , m2 , m3 , m0 + m2 + m3 , m0 + m1 + m2 , m1 + m2 + m3 ), (1.15)

U0 = m0 ,

U1 = m1 ,

U2 = m2 ,

U3 = m3 , (1.16)

U4 = m0 + m2 + m3 ,

U5 = m0 + m1 + m2 ,

U6 = m1 + m2 + m3 .

, m = ( 1 0 1 1

) , 䠠 U = ( 1 0 1 1 1 0 0 ). : m = ( 1 0 0 0

), U = ( 1 0 0 0 1 1 0 ).

, G , - .

G(7,4) (1.15) (1.16) (7,4)- (. 1.4).

, , , , , , .

 

. 1.4